Core Java 9 (LiveLessons (Indianapolis, Ind.), 2016)
"The first two lessons of Core Java LiveLessons, Second Edition, quickly review the history of Java and show you, step by step, how to install the software development environment. In lesson 3, you will learn how to do in Java what you already know in another programming language: write branches and loops, and work with numbers, strings, and arrays. Lesson 4 covers object-oriented programming. Java is thoroughly object-oriented, and the lesson shows you how to use built-in classes and how to build your own. Lessons 5 and 6 cover inheritance and interfaces as well as the lambda expressions, a powerful new feature of Java SE 8. Lesson 7 shows you what to do when your programs do the wrong thing. The lesson covers exception handling, logging, and debugging. In lesson 8, you will learn how to write generic code that works for many different data types. Lesson 9 puts those skills to work, when we examine the multitude of Java collections that allow you to organize your data in many ways. The final three lessons introduce the fundamentals of user interface programming in Java."--Resource description page